Graphene-Based Nanomaterials: From Production to Integration With Modern Tools in Neuroscience - Kitko, Kristina E.; Zhang, Qi (Frontiers in Systems Neuroscience, 2019)
The promises of nanomedicine are extensive. Graphene, the first true two-dimensional material to exist in isolation, is the type of new nanomaterial that results in interest for novel biomedical applications. From Michael Chrichton’s tragic protagonist in The Terminal Man to the recent growth in start-up companies seeking to transfer consciousness, the fictive present and future call to mind visions of devices that enable neural interfacing and control. Although these ideas may create questions as to ethics for neuroscience in the future, the current state-of-the-art for implanted devices is far more limited in scope. Progress in brain-computer interfaces holds great promise for patients following stroke (Ramos-Murguialday, Broetz et al. 2013), to control prosthetic limbs (Hochberg, Serruya et al. 2006, Donoghue, Nurmikko et al. 2007) , with the motor degeneration characteristic of Parkinson’s disease (Little, Pogosyan et al. 2013), and for a variety of other disorders and diseases (Chaudhary, Birbaumer et al. 2016). Graphene may be poised for incorporation into such devices. As the presence of graphene becomes more widespread and commonplace across the biomedical sciences, the relatively larger body of work detailing the biological effects of carbon nanotubes may serve as a template guiding the utility of graphene for biological applications (Kostarelos, Bianco et al. 2009). Graphene-based materials for interfacing with the peripheral nervous system have been reviewed elsewhere (Domínguez-Bajo, González-Mayorga et al. 2017). We instead focus on new directions for application to the central nervous system. This review is limited to preclinical applications, although graphene and graphene-based devices may someday advance to clinical implementation. We begin with an overview of graphene manufacturing advances, applications to hybrid materials systems as well as drug delivery strategies. This is followed by an overview of work performed with non-murine models. Finally, the interaction of graphene with murine neural systems, both in vivo and in-vitro is examined. Despite a sizable body of work, to date there remain many unresolved questions as to cytotoxicity and the mechanisms underlying the graphene-cellular interaction that must be addressed moving forward.